Internodal Analysis of Avicennia marina in the Western Arabian Gulf - Almahasheer, Hanan (Frontiers in Marine Science, 2021)
Estimating Avicennia marina growth via internodal analysis have not been done in this area. The node production in forty branches/axillary shoot in Syhat city, Saudi Arabia ranged from 6 to 9 nodes y-1 . and the annual cycles of the internodal length represents the branch growth rate in centimeters per year, which (ranged from 12 to 43 cm; median of 19 cm) for minima to minima point and (15 to 46.5 cm; median of 25.5 cm) for maxima to maxima point. The results obtained within the study is essential for several applications, from planning of restoration and monitoring activities to reproduction estimates via simple measurements.